2018
DOI: 10.1111/famp.12418
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Conflict Narratives in Emerging Adult Couples: Viewpoint and Gender Matter

Abstract: Healthy romantic relationships entail understanding the needs of the self and other when interpreting conflict events. Yet how couples make meaning around specific conflicts and their capacity to reflect on their own and their partners’ unmet needs is understudied. Using narratives, we examined destructive (e.g., extreme anger and break‐up anxiety) and constructive (e.g., perspective taking) interpretations of past romantic conflicts in 80 emerging adult heterosexual couples and the extent to which such interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 57 publications
(101 reference statements)
0
13
0
Order By: Relevance
“…For instance, in a study of older adult married couples, it was found heterosexual males were less likely to express underlying emotional needs, compared to their heterosexual female counterparts (Ermer & Proulx, 2020). Furthermore, because heterosexual females tend to be more focused on their romantic relationship goals, compared to heterosexual males, they often attempt to anticipate and address their male partner's needs (Feiring et al, 2020). Although speculative, it is possible that heterosexual couples develop a pattern by which when a male partner's need for reassurance of love heightens to the point where it becomes excessive, his female partner tends to become preoccupied with thoughts of how past or future responses might affect the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a study of older adult married couples, it was found heterosexual males were less likely to express underlying emotional needs, compared to their heterosexual female counterparts (Ermer & Proulx, 2020). Furthermore, because heterosexual females tend to be more focused on their romantic relationship goals, compared to heterosexual males, they often attempt to anticipate and address their male partner's needs (Feiring et al, 2020). Although speculative, it is possible that heterosexual couples develop a pattern by which when a male partner's need for reassurance of love heightens to the point where it becomes excessive, his female partner tends to become preoccupied with thoughts of how past or future responses might affect the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Given that these three topics tend to be seen as more difficult to resolve (Sanford, 2003;Williamson et al, 2013), it is possible that couples with these problems will report less marital satisfaction than the couples included here. Furthermore, jealousy, religious differences, and problems with relatives tend to occur earlier in romantic relationships, and if they cannot be resolved, may lead to dissolution of the relationship (Feiring et al, 2018;Kurdek, 1994;Reese-Weber et al, 2015). Although both the MCDS and the MARS couples represent a select group of couples in light of their high levels of marital happiness, it is notable that we did find group differences based on developmental stage.…”
mentioning
confidence: 65%
“…Given that these three topics tend to be seen as more difficult to resolve (Sanford, ; Williamson et al., ), it is possible that couples with these problems will report less marital satisfaction than the couples included here. Furthermore, jealousy, religious differences, and problems with relatives tend to occur earlier in romantic relationships, and if they cannot be resolved, may lead to dissolution of the relationship (Feiring et al., ; Kurdek, ; Reese‐Weber et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicts about unmet needs are a normative proximal risk factor for relationship aggression (e.g., Goncy & van Dulmen, 2016; Johnson et al, 2015; Lantagne & Furman, 2020). Narratives in which the self is the target of a perceived transgression from the partner are more likely to motivate a sense of injury and self-justified anger (Feiring et al, 2020; Kearns & Fincham, 2005). In contrast, narratives in which the self has caused harm to the partner are more likely to feature mitigating circumstances and self-justifications.…”
Section: Relationship Processes Related To Aggressionmentioning
confidence: 99%